How to Get Beyond the Zero-Sum Game Mentality between State and Non-State Actors in International Environmental Governance - Perez, Franz Xavier (Consilience, 2009)
This paper examines the participation of stakeholders in environmental policy formulation and implementation. After a short discussion of the main functions and challenges of environmental governance the paper addresses the issue of stakeholder participation and the claim of “democratic deficits” in international environmental governance. It stresses that while non-state actor involvement does not necessarily increase democratic legitimacy, it may nevertheless increase the quality of the environmental policy processes. It will then argue that certain international processes such as the UN Commission on Sustainable Development (CSD) have led to an unsatisfactory situation of non-state actor involvement where excessive formalization and proceduralization impede active interaction and input of expertise from non-state actors. It seems that the interaction between state and non-state actors in some of today’s international processes, such as the CSD, has led to a zero-sum gamewhere no party is really benefiting from the contributions of the other. This paper will suggest several changes to get beyond this zero-sum game mentality, including de-formalization of participation, replacement of generalist non-governmental organizations with those that specialize in specific fields, and reformation of the relationship between state and non-state actors so that each might come to see the other as a partner, not as a competitor. It will conclude by arguing that neither the alleged lack of an authoritative, effective central institution addressing the main environmental problems, nor the so-called “democratic deficit” is the main challenge to today’s international environmental governance, but the lack of political will. Political will, however, is not an absolute; it can and has to be stimulated. And this may be one of the most productive contributions that non-state actors can make.